Cholera outbreak trends in Nigeria: policy recommendations and innovative approaches to prevention and treatment - Eneh, Stanley; Onukansi, Francisca; Anokwuru, Collins; Ikhuoria, Ogechi; Edeh, Gabriel; Obiekwe, Sochima; Dauda, Zakariya'u; Praise-God, Awoyemi; Okpara, Chizaramekpere (Frontiers in Public Health, 2024)
Cholera, an acute diarrheal infection from ingesting contaminated food or water, remains a significant public health threat in Nigeria, especially in areas lacking safe water and sanitation. Characterized by severe watery diarrhea, cholera can cause dehydration and death if untreated. Historical data shows cholera's endemic nature in Nigeria, with notable outbreaks since 1970, including major ones in 1991, 1999, 2010, 2018, and 2024. According to a descriptive study in Nigeria, the 1991 outbreak reported 59,478 cases and 7,654 deaths, with a Case Fatality Ratio (CFR) of 12.9%. In 2010, there were 41,787 cases and 1,716 deaths, with a CFR of 4.1% across 18 states, mainly affecting impoverished communities and children. The 2018 outbreak had 43,996 cases and 836 deaths, with a CFR of 2% in 20 states, a 240% increase from 2017. By mid-2024, there were 1,579 suspected cases and 54 deaths (CFR 3.4%) in 32 states. This paper evaluates cholera trends in Nigeria and proposes effective preventive and treatment strategies. Policy recommendations highlight the need for improved WASH infrastructure, enhanced surveillance, and rapid response mechanisms. Innovative approaches like case-area targeted interventions (CATI) and increased public health education are crucial for mitigating future outbreaks and achieving the goal of reducing cholera deaths by 90% by 2030.